Śafār, capital of Himyar, Fifth Preliminary Report, February-March 2005. - Yule, Paul (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
In February–March 2005, the joint University of Heidelberg-Yemen team conducted a season of mapping at Zafãr. Major tasks included complementing the compilation of place-names of the different fields in the area. In this way, we obtain an instrument with which to identify fossil pre-Arabic place-names. Zafãr is not the largest archaeological site in the Yemen, but may well be the second largest one, after Mãrib. The large cliff of Zafãr/al-Dãhã turns out to owe its form to the great earthquake of 1982. The rectification of a Quickbird image documents in concrete fashion the soil erosion and other environmental changes in and around the ancient city. Vulture reliefs from the surrounding area show a new style, which appears to date to the 6th century, to judge from related images in Europe. Our recording is just keeping abreast of destruction mostly from building operations. The article will be available as a PDF in the near future.